LOKALITAS, ISLAMISITAS DAN GLOBALITAS:TAFSIR FALSAFI DALAM PENGEMBANGAN PEMIKIRAN PERADABAN ISLAM - Abdullah, M. Amin (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2012)
This paper attempts to consider how the history of world religions, including the history of Islamic civilization, always have, through and documenting the cultural encounter, i.e. the relationship between center and periphery and the experience of the encounter in the frontier. Two-ways relationship shaping a dyadic pattern, that is the encounter of Muslim with the local culture in which the regional and national states dimensions is being ignored, or vice versa, and also an encounter of Muslim with the nation states which forgetting the aspirations and local culture, yet to meet and to relate the two with international issues, either an encounter of religion and international community as well, is almost impossible to bring about the new problems within the dynamics of the global era today. Thus, the role of philosophical interpretation and contemporary Islamic philosophy is to provide a discern socio-cultural analysis in its interplay more complete and accurate between regional, national and mondial.